2020
DOI: 10.1002/tax.12316
|View full text |Cite
|
Sign up to set email alerts
|

Linnaeus's folly – phylogeny, evolution and classification of Sedum (Crassulaceae) and Crassulaceae subfamily Sempervivoideae

Abstract: Sedum, containing approximately 470 species, is by far the largest genus of Crassulaceae. Three decades of molecular phylogenetic work have provided evidence for the non‐monophyly of Sedum and many more of the 30 genera of Crassulaceae subfam. Sempervivoideae. In this study, we present a broadly sampled and dated molecular phylogeny of Sempervivoideae including 80% of all infrageneric taxa described in Sedum as well as most other genera of the subfamily. We used sequences of one nuclear (ITS) and three plastid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 83 publications
(204 reference statements)
7
54
1
Order By: Relevance
“…Moreover, phylogenetic studies of Crassulaceae have relied primarily on a limited set of chloroplast markers (e.g., matK, rps16, and trnL-trnF). Our comparative analyses, however, have shown that these chloroplast markers appear to be relatively low in nucleotide diversity (Figure 2), which may be partially responsible for the lack of phylogenetic resolution within Sempervivoideae (Mort et al, 2001;Messerschmid et al, 2020). Thus, to achieve better phylogenetic resolution, future studies of Crassulaceae should focus on molecular markers from more variable regions of the chloroplast genome, such as ccsA-ndhD, rps16-trnQ, rpl32-trnL, and trnH-psbA (Prince, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, phylogenetic studies of Crassulaceae have relied primarily on a limited set of chloroplast markers (e.g., matK, rps16, and trnL-trnF). Our comparative analyses, however, have shown that these chloroplast markers appear to be relatively low in nucleotide diversity (Figure 2), which may be partially responsible for the lack of phylogenetic resolution within Sempervivoideae (Mort et al, 2001;Messerschmid et al, 2020). Thus, to achieve better phylogenetic resolution, future studies of Crassulaceae should focus on molecular markers from more variable regions of the chloroplast genome, such as ccsA-ndhD, rps16-trnQ, rpl32-trnL, and trnH-psbA (Prince, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…The angiosperm family Crassulaceae, also known as the stonecrop family, belongs to the order Saxifragales and include 34 genera and approximately 1,400 species (APG IV, 2016;Messerschmid et al, 2020), which are predominantly perennial herbs, subshrubs, or shrubs (Thiede and Eggli, 2007). The species of Crassulaceae primarily occur in (semi-)arid and mountainous habitats of the temperate and subtropical areas (van Ham and Hart, 1998), and are distributed worldwide with centers of diversity in Mexico, southern Africa, Macaronesia, and the Himalayas (Mort et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations